“Aislamiento de bacterias rizosféricas diazotróficas de cultivadores de arroz (oryza sativa L.) con potencial biotecnológico en la región de san martín” - Ríos Ruiz, Winston Franz (2016)
Rice feeds more than 50% of the population worldwide, constituting a large energy input in low-income families. In Peru, the San Martin region was established as the first producer of rice with an area of 82 271 has produced 559 829 has with an average yield of 6.8 TN I ha. Year after year, the abuse of synthetic chemical fertilizers (N, P and K) is necessary to maintain high levels of grain yield, this causes alteration in the physical, chemical and biological soil quality. A sustainabte alternative is the use of beneficia! microorganisms with selected characteristics through his promotion of plant growth, this are called PGPRs (Plant Growth Promotore Rhizobacteria). The aim of the study was to isolate and characterize bacteria rice rhizosphere of Cacatachi and Picota zones in the region of San Martín, in addition to select and evaluate the main characteristics of plant growth. 60 strains were setected by diazotrofia, growing in Burk and MJV medium, characterized and then evaluated. A principal component analysis shows that there are 4 variables that explain the variance in the results. p7b1m, la2b2, la3c5m, p2b1m, p9b3m, la2b3, la3c3 and la5c5 strains had the highest contribution to the total variance. This analysis shows that to level of greenhouse evaluation will allow selecting those strains, which individually or collectively can be used as bio-fertilizers and bioprotectors to improve crop yield of rice, with lower doses of chemical fertilizers.